2016
DOI: 10.3390/app6110332
|View full text |Cite
|
Sign up to set email alerts
|

Further Investigation on Laminar Forced Convection of Nanofluid Flows in a Uniformly Heated Pipe Using Direct Numerical Simulations

Abstract: Abstract:In the present paper, laminar forced convection nanofluid flows in a uniformly heated horizontal tube were revisited by direct numerical simulations. Single and two-phase models were employed with constant and temperature-dependent properties. Comparisons with experimental data showed that the mixture model performs better than the single-phase model in the all cases studied. Temperature-dependent fluid properties also resulted in a better prediction of the thermal field. Particular attention was paid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Thus, the nanofluid specific heat can be defined from a thermal balance including the mixture rule. This equation has been widely used by [42][43][44] among other references.…”
Section: Specific Heatmentioning
confidence: 99%
“…Thus, the nanofluid specific heat can be defined from a thermal balance including the mixture rule. This equation has been widely used by [42][43][44] among other references.…”
Section: Specific Heatmentioning
confidence: 99%
“…For Al 2 O 3 -water-based nanofluids with a mean particle diameter of 47 nm, Equations (8) and (9) provided by Maïga et al [24] then used by Mintsa et al [25] have proven to be accurate in most configurations as shown by Sekrani et al [26] for laminar flows in an uniformly heated pipe. Equations for the dynamic viscosity µ and the thermal conductivity λ of the nanofluid write:…”
Section: Heat Transfer Fluid Propertiesmentioning
confidence: 99%
“…It was shown that the increase of rib height and nanoparticle concentration were beneficial to the heat transfer performance. Sekrani et al [11] studied the flow and heat transfer of nanofluids in horizontal passages using direct numerical simulation. They found that, compared with the single-phase model, the two-phase model provided higher prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%